Research on Carbon Emissions from the Steel Industry Based on Individual Sequence Method - Xu Junlong; Chen Qi; Ge Zhisong; Chen Yuyang (E3S Web of Conferences)
In some developing countries, the steel industry is the largest carbon emitter of all manufacturing industries. Huge quantities of energy consumption and carbon emissions are caused by the process of combustion, melting, roasting and heating processes. In this article, the key processes in the steel industry are sorted out, and the calculation model of carbon emissions in the individual sequence is established according to the greenhouse gas emissions generated by different processes, and the results are compared with the overall carbon emissions calculation method. The calculation model of carbon emissions in the individual sequence can be used for accounting of each process in steel industry. Then, according to this method, the government can further set carbon intensity quotas for each process. Compared with the method of overall carbon emission accounting, this method is more conducive to the formulation of effective energy-saving and emission reduction countermeasures for government departments because of the identification of key emission processes.